Effectiveness of Traditional Sports Games in Social Skills Development - Irfan Fadhil Syamsuddin; Yusuf Hidayat; C Carsiwan (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
The role of physical education in fostering student social skills has been explained through various literature studies. The purpose of this study was to determine the effectiveness of traditional sports games in developing social skills. The research method used was the experimental method using a one group pretest-posttest research design. The population of this study were 11th grade students at UPI Laboratory High School, totalling 17 students. The instrument used in this study was the Social Skills Scale for Adolescents. The game form used in this study consisted of 2 traditional sports games, namely Gobak Sodor and Boy-boyan, which were adapted to the development of social skills and physical education theory. The test used to test the hypothesis in this study was the paired sample t-test using SPSS version 27 with a significance level of a=0.05. The results showed that the traditional sports games Gobak Sodor and Boy-boyan are able to shape social skills of children, such as cooperation, responsibility, hard work, and care in the game. It concludes that the development of social skills requires a continuous learning process to obtain the goal.